1995
DOI: 10.1128/jvi.69.3.1645-1651.1995
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of human cytomegalovirus on integrated and unintegrated human immunodeficiency virus sequences

Abstract: Human cytomegalovirus (HCMV) has been implicated as a potential cofactor in human immunodeficiency virus type 1 (HIV-1)-related disease. Previously, we reported that HCMV inhibits HIV-1 RNA and protein synthesis in cells productively infected with both viruses but, in transient assays, activates an HIV-1 long terminal repeat-chloramphenicol acetyltransferase (LTR-CAT) construct introduced into the cell by transfection (V. Koval, C. Clark, M. Vaishnav, S. A. Spector, and D. H. Spector, J. Virol. 65:6969-6978, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In vitro, coinfection with CMV has been shown to upregulate HIV-1 expression in some cell types (39) but not in others (33). Recent studies show that CMV inhibits HIV-1 RNA and protein synthesis in nonlymphohemopoietic cells productively infected by both viruses (67), an effect mediated by interactions between HIV-1 and CMV gene products (37). Our results show that CT and ST, although readily infected by CMV, did not become susceptible to HIV-1 when challenged with both viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, coinfection with CMV has been shown to upregulate HIV-1 expression in some cell types (39) but not in others (33). Recent studies show that CMV inhibits HIV-1 RNA and protein synthesis in nonlymphohemopoietic cells productively infected by both viruses (67), an effect mediated by interactions between HIV-1 and CMV gene products (37). Our results show that CT and ST, although readily infected by CMV, did not become susceptible to HIV-1 when challenged with both viruses.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of these analyses have used cell lines that are permissive for HCMV but not normally permissive for HIV-1 infection. Some transfection/superinfection assays have also shown specific differences in the effects of HCMV on HIV-1 infection depending on the cell type used and the relative levels of HIV-1 Tat and HCMV IE gene products in the co-infected cells (Jault et al, 1994;Moreno et al, 1997) and have also suggested that activation of the HIV-1 LTR by HCMV depends on whether the LTR reporter construct used is integrated into host genomic DNA or not (Koval et al, 1995). However, such assays were carried out using HIV-1 pseudotypes in cell lines that are not normally permissive for HIV-1 infection (Koval et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by many studies that IE1 and IE2, either independently or synergistically, transactivate various promoters. These promoters include those regulating cellular expression of the gene for the 70,000-molecular-weight heat shock protein (hsp70), c-myc, c-fos, and c-jun, as well as the promoter for the human immunodeficiency virus (HIV) long terminal repeat (LTR) (3,4,21,31,55). IE1(p72) has been described as a transactivator for the HCMV major IE promoter (6) and for some cellular genes via NF-B (17,32,44,57).…”
mentioning
confidence: 99%